Model of convergence of stakeholders for mastitis control in Murrah buffaloes - DIXIT, V B; CHHABRA, R; TRIPATHI, H; KHURANA, S; SAXENA, N; SHRINET, G; SINGH, S (The Indian Journal of Animal Sciences, 2021)
A model of convergence was developed and tested for mastitis control at village level in Murrah buffaloes. Village Chindar of Fatehabad district of Haryana was selected purposively. For this study 100 farmers who were registered members of the milk cooperative society and were contributing milk daily, were purposively selected. Freshly calved buffaloes (100) from December, 2018 to February, 2019 owned by these farmers were selected randomly for this study. As per the plan of work for testing the model, different types of interventions were made by multiple agencies collaborating together for testing the model. In this study, 400 milk samples of 100 healthy buffaloes were tested for somatic cell count (SCC) by california mastitis test (CMT) and milk culture analysis. Culturally positive samples were treated according to antibiotic sensitivity test (ABST) report. Besides interventions like trainings, public health campaigns, demonstration of CMT to the farmers was done individually. The experiment was repeated after 60 days by testing the milk samples for SCC and treating culturally positive samples according to ABST report which lead to decrease in SCC to the tune of 32%.